Experimental study and design of experiment using statistical analysis for the development of geopolymer matrix for oil-well cementing for enhancing the integrity - Rahman, S.H.A. (MDPI AG, 2021)
This paper presents an experimental investigation on geopolymer cement formulations for enhancing oil-well integrity. Fresh slurry properties, mixability, density, free-water, and rheology were determined for possible field applications. The compressive strength and expansion characteristics were studied for the durability and integrity of the well system. Mix formulations complied with the requirements of API RP 10B-2. All formulations showed homogeneous mixability, rheological properties, the plastic viscosity (PV), and yield point (YP) were increased from 48 cP to 104 cP and 3.8 N/m2 12.4 N/m2, respectively, with the increase of the dosage of elastomeric type expandable material (R additive). The highest compressive strength of 15 MPa was obtained using 10 R additive in the mix-blend after 60 days of curing. Increasing the amount of R additive provides the optimum strength at 10.4 MPa with design 2, 3, and 4. The linear expansion was increased to about 1 at 60 days with 20 and 25 of the R additive dosage. Design of Experiment (DOE) was performed for setting three factors: curing time (A), curing temperature (B), and concentration of R additive (C) to optimize the linear expansion (response). Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.